The Ruling of the Friday Prayer (Salat Al-jumu’ah) According to Twelver Shia, in the Absence of Imam - Agamoglanov, Hilal (Scholarya Demo Journal of Ruby, 2020)
One of the wajib (obligatory) acts of worship in Islam is the Salat alJumu’ah (Friday prayer). According to Shia jurists, Friday prayer, in which participation of people is essential, is a prayer that organized by an infallible person a prophet or an imam. Making a consensus on this ruling, none of the past and present jurists opposed it. In general, the ruling of this salat during the occultation period of the infallible Imam is disputable amongst scholars of Imamiyya Shia. Great jurists of the formative period, such as Sallar, Ibn Idris, Sharif Murtaza, Shaykh Tusi, and Allamah Hilli considered the Friday prayer as haram (forbidden). The vast majority of Imamiyya jurists, however, are of the opinion that this prayer is individual obligation (wajib al-ayni) or optional obligation (wajib al-takhyiri). During the 10-13th centuries there were some Imamiyya jurists who regarded Friday prayer to be individual obligation, but it was a common view especially among the 14-17th century jurists. Gradual political lifting of the Imamiyya sect and foundation of Safavid dynasty during that period have played a key role in this decision. Shaykh Mufid, Zaynaddin bin Nureddin Amili, Muhammad bin Ali Amili, Yusif Bahrani, Fayz Kashani, Abul-Fath Karadjuki, Imamaddin al-Tabari, Allamah Majlisi and Hurr Amili are from the scholars who considered this prayer individual obligation. Several old jurists, such as Shaykh Tusi, Allamah Hilli, and also Shaykh Abu Salah Halabi, who changed their opinion saying that Friday prayer is permitted in the absence of the Imam, as well as other middle and later period jurists including Shahid Sani, Muhammad bin Ali Amili, Muhaqqiq Hilli, Shaykh Ali bin Hussein Karaki, Shaykh Kashif al-Ghita and Shaykh Muhammad Hasan Najafi decreed that Friday prayer is optional obligation, which allowed to choose between Friday and midday prayers.